Therapeutic Peptides Methods and Protocols - Nixon, Andrew E.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2014)
Therapeutic Peptides: Methods and Protocols features biological methods for the preparation of peptide phage display libraries using both filamentous and lytic phage.  With contributions from renowned authors in the field, the book also explores selection and screening of the prepared peptide libraries for peptides with the desired function and the subsequent characterization of the identified peptides.  Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Practical and dependable,  Therapeutic Peptides: Methods and Protocols is an ideal guide for researchers from all backgrounds seeking methods for the identification of therapeutic peptide candidates.
Design of Phage-Displayed Cystine-Stabilized Mini-Protein Libraries for Proteinaceous Binder Engineering -- Construction of a Filamentous Phage Display Peptide Library -- Engineering Bio-Active Peptide-Based Therapeutic Molecules -- T7 Lytic Phage-Displayed Peptide Libraries: Construction and Diversity Characterization -- Affinity Selection Using Filamentous Phage Display -- Bioprospecting Open Reading Frames for Peptide Effectors -- Identification of Ideal Peptides for Heterovalent Ligands -- Substrate Phage Display for Protease Substrate Sequence Characterization: Bovine Factor Xa as a Model System -- Engineering Peptide Therapeutics Using MIMETIBODY™ Technology -- Evaluation of Peptides as Protease Inhibitors and Stimulators -- Assessment of Antimicrobial (Host Defense) Peptides as Anti-Cancer Agents -- Peptide Labelling Strategies for Imaging Agents -- Peptide Optimization and Conjugation Strategies in the Development of Molecularly Targeted Magnetic Resonance Imaging Contrast Agents -- Evaluation of Prenylated Peptides for Use in Cellular Imaging and Biochemical Analysis -- Ultraviolet Absorption Spectroscopy of Peptides -- Fluorescence Spectroscopy of Peptides -- Circular Dichroism of Peptides -- Fourier Transform Infrared Spectroscopy of Peptides.
Keywords: Pharmacology; Pharmacology/Toxicology.